Transformer Differential Protection Method for Recognition between Power Transformer Internal Defects and Inrush Current: A Comprehensive Review of Detection Techniques - Atiyah, Wael Abdulhasan; Karimi, Shahram; Moradi, Mohamad (Applied Science and Engineering Progress, 2025)
The cornerstone of any electric power system lies in its power transformers, as their seamless operation is crucial for network reliability. Instant disconnection from the grid is imperative upon detecting any faults to prevent cascading issues. However, distinguishing between fault conditions, like inrush current, which necessitates caution rather than immediate action, poses a challenge for effective protection schemes. This dilemma can lead to relay malfunctions, further jeopardizing system integrity. This paper delves into a thorough analysis and comparison of various methods employed in differential protection to discern between internal faults and inrush currents, aiming to enhance system resilience. This comprehensive review explores the efficacy of intelligent techniques, hybrid approaches, and traditional methods in fault detection. By shedding light on the strengths and limitations of each method, researchers in this domain can glean insights to innovate and address the deficiencies of existing strategies in tackling internal faults and inrush currents detection. Ultimately, this endeavor seeks to fortify the reliability and stability of power systems in the face of dynamic operational challenges.